Grammatical Errors Committed by Students in Writing Cause and Effect Paragraphs - Widyasari, Ni Putu; Ramendra, Dewa Putu; Utami, Ida Ayu Made Istri (STKIP AGAMA HINDU SINGARAJA, 2022)
The purpose of this study was to identify the grammatical errors and analyze the sources of grammatical errors committed by students in writing cause and effect paragraphs. This research used a mixed-method design as the research design. The data were collected through document collection of mid-term tests and final tests. The subjects of this study were students in two classes of the English Language Education Program. The results of this study showed that the types of grammatical errors in students' writing were omissions 54 errors (44%), misformation 37 errors (31%), addition 28 errors (23%), and misordering 3 errors (2%). The total errors committed by students in their paragraph writing were 122 errors. Meanwhile, the source of errors in students' writing was caused by intralingual transfer 82 (67%), interlingual transfer 35 (29%), and communication strategies 5 (4%). In writing, it is encouraged to check grammar through grammar checking that are available in order to reduce grammar mistakes and make the massage of the writing clearer. Teachers are encouraged to pay attention to students’ grammar and use teaching technique that can improve students’ grammar.